2005
DOI: 10.1126/science.1117756
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Proton Transfer Through Water Bridges in Acid-Base Reactions

Abstract: The proton transfer mechanism between aqueous Brønsted acids and bases, forming an encounter pair, has been studied in real time with ultrafast infrared spectroscopy. The transient intermediacy of a hydrated proton, formed by ultrafast dissociation from an optically triggered photoacid proton donor ROH, is implicated by the appearance of an infrared absorption marker band before protonation of the base, B-. Thus, proton exchange between an acid and a base in aqueous solution is shown to proceed by a sequential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

30
554
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 511 publications
(585 citation statements)
references
References 32 publications
30
554
0
1
Order By: Relevance
“…For example, a recent study of small NO + (H 2 O) n clusters investigated how the shape of h-bonded network controls proton-coupled water activation in HONO formation in the ionosphere [16]. Sequential PT through water bridges in acid-base reactions has been studied by time-resolved experiments in which the reaction has been initiated by an optical trigger exciting the photoacid [17]. Resonant ionization spectroscopy of gas-phase h-bonded clusters was employed to investigate proton versus hydrogen transfer pathways [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study of small NO + (H 2 O) n clusters investigated how the shape of h-bonded network controls proton-coupled water activation in HONO formation in the ionosphere [16]. Sequential PT through water bridges in acid-base reactions has been studied by time-resolved experiments in which the reaction has been initiated by an optical trigger exciting the photoacid [17]. Resonant ionization spectroscopy of gas-phase h-bonded clusters was employed to investigate proton versus hydrogen transfer pathways [18].…”
mentioning
confidence: 99%
“…Our findings illustrate that water has a dramatic effect on PT pathways, not only by serving as a wire for proton transport, but also by shutting down other PT routes. In our model systems, an outermost ionized water molecule acts as an acid (activated by an ionization event), and the nucleobase -as a base, whereas other waters may participate in PT either as spectators or as intermediate proton acceptors, as shown recently in photo induced acid-base reactions [17]. We explain the remarkable similarity between the appearance onsets in solvated mU and thymine, as well as insensitivity of the onsets and shapes of the appearance curves on the cluster sizes to the fact that the lowest ionized states in which the hole is localized on the solvent correspond to the surface states, i.e., water molecules acting as proton donors only.…”
mentioning
confidence: 99%
“…For example, it was shown that intermolecular couplings make water molecules behave collectively, and in this way they dramatically accelerate redistribution of vibrational and thermal energy through the hydrogen-bonded water network, [26][27][28] play essential role in the water mediated proton transfer [29][30][31] and other biologically relevant processes. 6 Nonetheless, in spite of a considerable effort in studying the dynamics and intermolecular coupling of water molecules bound to the different interfaces, the overall picture still remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Powerful pump-probe spectroscopy [27][28][29] allows for the direct determination of the dynamics of the electron-hole pairs, charge separation, intraband relaxation, multiple excitations, multi-exciton generation, and Auger recombination-all of which govern the photophysical processes in semiconductor CIGS thin films [26,30] or in other semiconductors such as PbS quantum dots for solar cell applications [31].…”
Section: Introductionmentioning
confidence: 99%